Relative importance of left atrial reservoir strain compared with components of the HFA-PEFF score: a cross-sectional study - Kim, Minkwan; Bae, SungA; Park, Jin Hye; Jung, In Hyun (Frontiers in Cardiovascular Medicine, 2023)
Background The relative importance of left atrial reservoir strain (LASr) regarding the Heart Failure Association Pre-test assessment, Echocardiography and natriuretic peptide, Functional testing, Final etiology (HFA-PEFF) score, a diagnostic tool for patients with heart failure with preserved ejection fraction (HFpEF), remains unclear. We aimed to identify the relative importance of LASr compared with variables associated with HFpEF and HFA-PEFF scores. Methods Between August 2021 and July 2022, we obtained retrospective data from the participants visiting a single cardiovascular center with subjective symptoms of heart failure, such as dyspnea or chest discomfort. In total, 2,712 participants with sinus rhythm and ejection fraction of more than 50% were enrolled. Multivariable logistic regression analysis, random forest analysis, and supervised machine learning algorithms were performed to identify the relative importance of LASr to the HFA-PEFF score. Results The average HFA-PEFF score was 2.4 ± 1.6 points. Two hundred and thirty-eight participants had 5 or 6 points. LASr showed a moderate correlation with the HFA-PEFF score (r = −0.50, p < 0.001). Impaired LASr < 25.2% was an independent variable affecting a high HFA-PEFF score with traditional diastolic function parameters and components of the HFA-PEFF diagnostic algorithm. The odds ratio (OR) [1.74, 95% confidence interval (CI) 1.23–2.47] for LASr was higher compared to that of left ventricular global longitudinal strain (OR 1.59, 95% CI 1.14–2.21), septal E/e’ (OR 1.23, 95% CI 0.85–1.77), and relative wall thickness (OR 1.20, 95% CI 0.76–1.89). LASr was also a relatively more important variable in estimating a high HFA-PEFF score than TR-Vmax, septal E/e’, septal e’, left ventricular mass index, and relative wall thickness, the major echocardiographic components of the HFA-PEFF score. Conclusions LASr is an important factor with components of the HFA-PEFF score and is a useful tool to assess patients with HFpEF. Clinical Trial Registration URL: https://clinicaltrials.org. Unique identifiers: NCT05638230.